Experimental study of cooling systems with intensification in field of inertial forces - V. V. Shalay; K. V. Shcherban (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses the results of an experimental study of cooling systems with intensification of inertial forces in a field, obtained on a modernized experimental bench. This stand made it possible to study the efficiency of heating the components of liquid fuel of a hydrocarbon coolant in the field of inertial forces and verify the results obtained in ANSYS.